(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
The existing great strides on cultural feminist demonstration towards developing techniques to preventing domestic violence, and other forms of social construct against women, navigate through resistance and pragmatic ingenuity as a commendable role in appraising the songs of Bob Marley, owing to the constructive criticism the diction of his lyric songs possess. The Jamaican society where Marley’s songs are set is a physical, social and economic violence society which is against women, most especially the poor women of colour, who are perpetuated in part by top down globalization. This article demonstrates how resistance permeates through pragmatic ingenuity and feminist metaphors to embellish and address a set of approaches to legal scholarship rooted in feminist and anti- racist critical traditions, thereby reconceptualizing the human right problems facing Black women who migrate between the United States and Jamaica. Marley’s cultural feminist song “No Woman No Cry” depicts that Jamaica (Caribbean) women have become the private solution to the public problem of fundamental race, class, and gender inequalities in United States. Admissibly, critical race feminist approach requires prospective strategies to be pragmatic and metaphorical, as well as theoretical. It, however, requires a difficult process of building coalitions among women and men who sometimes resist seeing their common interest being trampled on. This scholarly work, therefore, aims at adopting post-colonial feminist theory as a theory that permeates through the subject matter of Marley’s lyric song and attempts to give a critical appraisal of the song from the post- colonial perspective through his poetic diction of the post- colonial feminist society.